Improving software maintainability through aspectualization - Mortensen, Michael, author; Ghosh, Sudipto, advisor; Bieman, James M., advisor (Colorado State University. Libraries, 2009)
The primary claimed benefits of aspect-oriented programming (AOP) are that it improves the understandability and maintainability of software applications by modularizing cross-cutting concerns. Before there is widespread adoption of AOP, developers need further evidence of the actual benefits as well as costs. Applying AOP techniques to refactor legacy applications is one way to evaluate costs and benefits. Aspect-based refactoring, called aspectualization, involves moving program code that implements cross-cutting concerns into aspects. Such refactoring can potentially improve the maintainability of legacy systems. Long compilation and weave times, and the lack of an appropriate testing methodology are two challenges to the aspectualization of large legacy systems. We propose an iterative test driven approach for creating and introducing aspects. The approach uses mock systems that enable aspect developers to quickly experiment with different pointcuts and advice, and reduce the compile and weave times. The approach also uses weave analysis, regression testing, and code coverage analysis to test the aspects. We developed several tools for unit and integration testing. We demonstrate the test driven approach in the context of large industrial C++ systems, and we provide guidelines for mock system creation. This research examines the effects on maintainability of replacing cross-cutting concerns with aspects in three industrial applications. We study several revisions of each application, identifying cross-cutting concerns in the initial revision, and also cross-cutting concerns that are added in later revisions. Aspectualization improved maintainability by reducing code size and improving both change locality and concern diffusion. Costs include the effort required for application refactoring and aspect creation, as well as a small decrease in performance.
Keywords: aspect-oriented programming; aspectualization; refactoring; software maintenance; computer science